Percieved Professional Competency Level and Job Performance of Block-level Extension Agents in Bhutan - Samdrup Rigyal; Chaicharn Wongsamun (Journal of International Agricultural and Extension Education, 2011)
The primary purpose of this study was to identify the perceptions of extension agents in Bhutan on the professional competencies they considered important and possessed. The results of the study showed that extension agents have lower confidence on the technical knowledge they possessed in the respective subject areas. The other priority training requirements for extension agents identified by the study were on: how to conduct situational analysis, ability to prepare visual aids, finding ways to encourage farmers to adopt innovations, visualizing future extension prospects and problems, introducing new extension methods, building confidence in meeting objectives, creating awareness of the government policy and ability to organize and present a seminar. The junior extension agents have a higher confidence on some competencies compared to their seniors. Therefore, the departments of agriculture, animal husbandry and forestry in the Ministry of Agriculture should regularly conduct training needs analysis and provide in-service training to update the knowledge and skills of extension agents.
Keywords: extension agent; professional compentency; training; perception; job performance